2021
DOI: 10.1177/03635465211015687
|View full text |Cite
|
Sign up to set email alerts
|

Defining Clinically Significant Improvement on the Patient-Reported Outcomes Measurement Information System Test at 1-Year Follow-up for Patients Undergoing Hip Arthroscopy for the Treatment of Femoroacetabular Impingement Syndrome

Abstract: Background: Although minimal clinically important difference (MCID), Patient Acceptable Symptom State (PASS), and substantial clinical benefit (SCB) have been defined for hip-specific legacy patient-reported outcome measures, these metrics have not been defined for the Patient-Reported Outcomes Measurement Information System (PROMIS) instruments for patients undergoing hip arthroscopy. Purpose: To define the MCID, PASS, and SCB thresholds for the PROMIS Physical Function (PF) computerized adaptive test (CAT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Using these values, we found regardless that a notable amount of patients report clinically significant outcomes for PROMIS-PF (71.4%) and PROMIS-PI (54.0%). However, using the values reported by Bodendorfer et al, 33 for example, these numbers would rise to 92.1% for PROMIS-PF and 88.9% for PROMIS-PI. This discrepancy is likely due to differing methodologies, although it could also potentially be explained by the unfavorable area under the curve (0.57) for PROMIS-PI reported by Kuhns et al It is important to be mindful of this observation and interpret the CIOV results in our study, particularly those relating to PASS for PROMIS-PI, with appropriate caution.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Using these values, we found regardless that a notable amount of patients report clinically significant outcomes for PROMIS-PF (71.4%) and PROMIS-PI (54.0%). However, using the values reported by Bodendorfer et al, 33 for example, these numbers would rise to 92.1% for PROMIS-PF and 88.9% for PROMIS-PI. This discrepancy is likely due to differing methodologies, although it could also potentially be explained by the unfavorable area under the curve (0.57) for PROMIS-PI reported by Kuhns et al It is important to be mindful of this observation and interpret the CIOV results in our study, particularly those relating to PASS for PROMIS-PI, with appropriate caution.…”
Section: Discussionmentioning
confidence: 84%
“…We also used PROMIS-PF and PROMIS-PI CT scores, which assess for global functioning and patient quality of life while correlating well with the hip legacy scales and providing benefits such as decreased survey burden as well as mitigation of floor and ceiling effects. 33,[53][54][55][56] The most notable limitations of this study are the small sample size (63 patients) and significant loss to follow-up (34.4%). Our numbers are slightly lower yet still comparable to other published works in the field of isolated acetabuloplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that patients with younger age and lower BMI preoperatively were more likely to attain these thresholds. 39 Patients with symptomatic acetabular dysplasia were evaluated by Li et al in a prospective study. 40 A total of 57 patients underwent periacetabular osteotomy and were assessed preoperatively and at a mean of 1.5 years postoperatively with the PROMIS PF and PI CATs along with several legacy PROMs (including HOS-Pain, HOS-ADL, and mHHS).…”
Section: Promis In Hip Conditionsmentioning
confidence: 99%
“…They found that patients with younger age and lower BMI preoperatively were more likely to attain these thresholds. 39…”
Section: Promis In Hip Conditionsmentioning
confidence: 99%